اثر المتغيرات الفردية لدى طلبة الصف الثاني عشر وآبائهم في مستوى الوعي المهني : دراسة حالة في منطقة الباطنة جنوب بسلطنة عمان = The impact of individual variables among twelfth grade students and their parents on the level of professional awareness: a case study in al batinah region south the Sultanate of Oman - Al-Kindi, AdilAdil Mohammed; Al-Hidabi, Dawood Abdulmalek Yahya; AlRiymi, Ahmad Jumaa (Yayıncı OCERINT International Organization Center of Academic Research, 2020)
This quantitative study discussed the effect of individual variables among students and their parents on the level of occupational awareness. The problem emerges from the presence of many individual variables that affect the student's professional choice, including the student's knowledge of himself and his capabilities and his ability to make the right professional decision, in light of variables: gender, educational level of the father, family income level, age of the father. Therefore, the aim of the study was to discuss the effect of variables (gender, educational level of the father, level of family income, age of the father) in finding statistically significant differences in occupational awareness among twelfth grade students and their parents. I followed the descriptive analytical research methodology. The study population consisted of all 12th graders in the region. They are (6125) male and female students, distributed among (37) schools in six states. The sample consisted of (312) students. The number of males (152) and females (160). These students meet their parents (312). A unified scale for occupational awareness for students and parents was designed, it included (47) items distributed in six areas: the field of vocational guidance activities, the direction towards work, professional inclinations and capabilities, professional decision-making, professional attention, and vocational planning. Statistical treatment: Descriptive analysis, (T) test, and ANOVA (One-Way) test were used. The results showed that there were statistically significant differences in occupational awareness among twelfth grade students according to the gender variable and in favor of females. There are no statistically significant differences in Professional awareness among the twelfth grade students according to the variables (the educational level of the father, the level of the family's income, and the age of the father) There are no statistically significant differences in the professional awareness of the fathers of the twelfth grade students according to the variables (the educational level, the level of family income, and age).